Pembuatan Kata Kunci Otomatis Dalam Artikel Dengan Pemodelan Topik - Lucky Adhikrisna Wirasakti; Rony Permadi; Anggit Dwi Hartanto; Hartatik Hartatik (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
This study aims to determine the appropriate keywords to be used in the publication of articles on the blog, the Latent Dirichlet Allocation (LDA) Model, an opportunity model which will produce a variety of different topics. Beginning with taking data from articles / blogs, then cutting articles per section and doing data preprocessing, and changing vector data into corpus to be modeled with LDA, then grouping with K-means to search for topics with higher assistance. The results of quoting from the LDA Model obtained 4 topics with 8 words with the highest probability value, mesin (0.09375857), maksimal (0.064600445), mazda (0.10009629), varian (0.07572112), cx-8 (0.10170187), mazda (0.101048954), mobil (0.09820121), dan mazda (0.05679208)